(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Successful bone tissue reconstruction needs to take into account multiple aspects ranging from the selection of biocompatible implant materials to complex biological mechanisms guiding bone tissue repair. All these factors are also essential for new additive manufacturing technologies such as 3D (bio)printing of bone constructs. So far mainly acellular material based 3D constructs are generated by 3D printing. In this context this presentation will emphasize how 3D printing technologies can profit from the cellular interaction during bone repair and vascularization leading to self-assembly of vascularized bone tissue in 3D bone constructs. In combination with 3D manufacturing technologies such as extrusion based printing and digital light processing technologies, this will enable to generate larger complex bone constructs in the future. First steps are made in bone tissue reconstruction by bioprinting including the development of bioinks and solid bone scaffolds. However, complex technological challenges still exist and need to addressed by interdisciplinary approaches in the future.